Toxicological impact on environmental matrices by trace elements from gold mining in the biogeographic Choco, Colombia. (2019)
Mining and technology industries are using trace elements throughout the world to manufacture new technologies and products for daily use which are released into the environmental until reaching biological and environmental compartiments. Other the anthropogenic factors, such as extraction of minerals, wood an agriculture, modify the natutal levels of metals in earth´s crust. Among the trace elements, heavy metals are considered the main pollutants because they remain for long periods of time in the environment, they cannot metabolized, but if they bioaccumulate in the tissues of different organisms of terrestrial and aquatic ecosystems causing lesions such as, decrease in the production of sperm, nervous system, bones, kidneys, neurologicals, cancer, pulmonary diseases, motor and conigtive dysfunción, among others, are derivated from metals such as Pb, Cd, Hg, As, Ni, Cu, Rb, Cs, Ta, and some of the rare elements of the earth. In the Atrato basin, tropical rainforests house exceptional wildlife species, placing it among one of the richest sites in biodiversity on the planet, currently threatened by massive gold mining, one of the main sources of mercury pollution (Hg), it is a harmful pollutant released into the environment, it represents a risk to human health and ecosystems. The first objective of this study was to evaluate the levels of total Hg (T-Hg) in human hair, fish, sediments and air; and determine the risks based on the consumption of fish by ingestion of T-Hg in the region of Choco biogeographical, a site of high global biodiversity located at the Colombian Pacific. Mercury concentrations in hair were measured in two places, Quibdo, the capital of the department, and Paimado, a riversine community. The median value of T-Hg in human hair in Quibdo was 1.26 µg/g (range: 0.02-116.40 µg/g), while in Paimado it was 0.67 µg/g (range: 0.07-6.47 µg/g). Mercury levels in locations examined were weakly associated with height (r=0.145, P=0.024). The levels of THg in the air in Quibdo were high inside gold shops, being up to 200.9 times higher than the reference site. Mercury concentrations in fish from Atrato River were above WHO limit (0.5 µg/g), with the highest levels in Pseudopimelodus schultzi, Ageneiosus pardalis, Sternopygus aequilabiatus, Rhamdia quelen and Hoplias malabaricus, while the lowest appeared in Cyphocharax magdalenae and Hemiancistrus wilsoni. Based on fish consumption, these last two species offer low risk to human health. Sediment samples from fifty different sites of the Atrato River showed low concentrations of T-Hg, with little variability between stations. However, contamination factors (CF) revealed moderate pollution in 44% of sampling sites along the river. In addition to Hg, other trace elements threaten this site of high biodiversity. To protect this natural resource, the Constitutional Court of Colombia declared that the river as a subject of legal rights. The objective of this study was to quantify trace elements in sediments and fish from the Atrato basin, assessing their environmental and human health risk. Forty-two trace elements were quantified using ICP-MS. Thirty-one elements increased their concentration downstream of the river. The CF suggests that the sediments were moderately polluted by Cr, Cu, Cd and heavily polluted by As. Most stations had higher Cr (98%) and Ni (78%) concentrations greater than the criterion of Probable Effect Concentration (PEC). Together, toxic elements generate a pollution Load Index (PLI) and a potential ecological risk index (RI) that categorized 54% of the sediments as polluted and 90% as moderate polluted, respectively. Hemiancistrus wilsoni, a low trophic guild fish species, had the greater average levels of Ni, Cu, As and Cd, among other elements. Rubidium and Cs showed a positive correlation with the fish trophic network, suggesting that these two metals are biomagnified according to the food chain. The Hazard Quotient (HQ) for As was greater than 1 for several species, indicating a potential risk to human health. In conclusion, pollution by Hg is widespread in the Biogeographic Choco, collectively, the data suggests that the extraction of gold carried out in this area of high biodiversity releases toxic elements that decline the quality of sediments in the Atrato River, incorporationing in the trophic chain which constitutes a great threat on the health of human and the environmental due to the consumption of fish, altering the chances of survival of species in impacted ecosystems, due to this urgent legal and civil actions should be implemented to stop massive deforestation driven by the mining, enforcing the right of the Atrato River, protecting of the populations and preserving this site of high biodiversity, government actions must be applied to anthropogenic activities.